THE EFFECTS OF ALLOPURINOL ON REDOX SENSITIVE TRANSCRIPTION FACTORS, PRO-INFLAMMATORY CYTOKINES AND HEME OXYGENASE-1 IN ACETIC ACID-INDUCED COLITIS IN RATS - Demirel, Ulvi; Yalniz, Mehmet; Orhan, Cemal; Tunc, Nurettin; Sahin, Abdurrahman; Tuzcu, Mehmet; Bahcecioglu, Ibrahim Halil (Carbone Editore, 2018)
Introduction: Oxidative stress plays an important role in pathophysiology of inflammatory bowel diseases. We aimed to investigate the effects of antioxidant allopurinol (AP) and the potential mechanisms leading amelioration upon acetic acid induced colitis. Materials and methods: Twenty-eight rats were divided in four groups. Control rats received 1 mL of NaCl (0.9%). In the AA group rats received 1 mL of 5% (v/v) acetic acid. The rats in the AAAP group received 1 mL of 5% (v/v) acetic acid. Additionally these rats received 100 mg/kg AP. AP group rats received only 100 mg/kg AP. Histopathological, biochemical and western blot analysis were done. Results: In the AA group, colonic injury scores, malondialdehyde (MDA), NF-kappa B p65, TNF alpha, COX2, AP-1 and IL-6 levels were significantly higher than in the control group (P<0.05). In the AAAP treatment group the colonic injury scores, MDA, NF-kappa B p65, TNFa, COX2, AP-1 and IL-6 levels significantly decreased when compared to the AA treated rats (P<0.05). The expression of HO-1 in the AAAP group significantly increased when compared to the AA treated rats (P<0.05). Conclusion: Intra colonic acetic acid instillation causes severe intestinal injury accompanied to increased oxidative stress. AP treatment ameliorates this injury by overcoming oxidative stress and regulating cellular redox balance in favor of antioxidant defense mechanisms probably via manipulation of redox sensitive transcription factors.
Keywords: Oxidative Stress; Allopurinol; Acetic Acid; Colitis; Redox Sensitive Transcription Factors